KETIDAKBERLANJUTAN EKONOMI PURNA PEKERJA MIGRAN PEREMPUAN DALAM ANALISIS EMPAT TINGKATAN SOSIOLOGIS - Ramlafatma, Ramlafatma (Nusantara Hasana Journal, 2025)
The phenomenon observed in the field is that many female migrant workers who have worked abroad still lack productive continuity, resulting in no significant improvement in the economic conditions of their families. They return to their homeland because their work contracts have expired. Although they have gained considerable work experience abroad, the lack of capital upon their return renders them unproductive once again. Repeated departures as female migrant workers do not have an impact on improving their families’ economic conditions. In addition, the attitude of their families, who do not appreciate the achievements of these female migrant workers, causes fatalism, apathy, parochialism, and dependency among female migrant workers. This condition ultimately leads to a cultural orientation of not needing to try too hard. The method used is a qualitative method that provides descriptive data or explanations related to facts in the field. The results obtained show that the analysis in four (4) sociological levels can be described in four (4) levels of study, namely: (1) Subjective micro study, (2) Objective micro study, (3) Objective macro study, and (4) Subjective macro study. Each level of study is explained as follows: (1) Female retired migrant workers and economic unsustainability from the perspective of Neo-Freudian personality theory, (2) Interactions between female returning migrant workers and economic unsustainability from the perspective of Simmel’s interaction theory, (3) Female retired migrant workers social structure and economic unsustainability from the perspective of structural theory, and (4) Female retired migrant workers culture and economic unsustainability from the perspective of Max Weber and David McClelland.